Engaging in physical activity instead of (over)using the smartphone: An experimental investigation of lifestyle interventions to prevent problematic smartphone use and to promote mental health - Precht, Lena-Marie; Mertens, Franziska; Brickau, Debora S.; Kramm, Romy J.; Margraf, Jürgen; Stirnberg, Jan; Brailovskaia, Julia (Journal of public health, 2024)
Aim Tendencies of problematic smartphone use (PSU) have risen during the past decade. As PSU is consistently linked to mental health issues, measures to prevent its appearance and to promote mental health are urgently required. Subject and Methods The present study investigated the impact of three interventions on health behavior, PSU, positive mental health (PMH), and depression and anxiety symptoms. Overall, 503 persons from Germany ( M age = 29.19, SD age = 10.51, range: 18–79) participated in the study. Over 14 days, the three experimental groups (a) reduced their daily smartphone use time by 60 minutes, (b) increased their daily level of physical activity by 30 minutes, and (c) combined both measures. The control group continued its behavior as usual. Outcomes were assessed via online surveys at five measurement time points (baseline, intermediate, post-intervention, and 1 and 3 months after the intervention). Results All interventions resulted in a significant increase in weekly physical activity and in reduced symptoms of PSU, depression, and anxiety. Furthermore, the smartphone reduction and the combination of both measures contributed to a significant reduction of participants’ daily smartphone use and higher levels of PMH. The effects of the reduction of smartphone use time and its combination with increased physical activity were more stable in the longer term than the increase in physical activity only. Conclusion Combined with an increase in physical activity, the reduction of smartphone use time could serve as an efficient and cost-effective measure for the prevention of PSU and the promotion of mental health.